Avaliação da função motora de crianças com hidrocefalia - Costa, Aida Carla Santana de Melo (2010)
Motor Function Evaluation of Hydrocephalus Children Background: Hydrocephalus constitutes a pathological condition that is manifested through signals and symptoms, including neurological and motor deficits that can result functional ability limitations. However, there are few studies that show the motor function of children with this illness. Objectives: To evaluate the kinetic and functional framework of hydrocephalus children; to identify the condition of muscle tone; to check the static and dynamic functional activities; to verify the association between tone alterations and functional activities in hydrocephalus children. Methods: A cross-sectional, descriptive, exploratory and field study, using qualitative and quantitative approach, performed at the University Hospital in Aracaju city, from August 2009 to March 2010. Results: From 50 evaluated children, 30 (60%) had hypertonia; 10 (20%) were hypotonic; and 10 (20%) showed no muscle tone alteration. The age average was considerably lower in hypertonic children and higher in hypotonic and without tone alteration children. The average of carried through surgeries was more expressive in hypertonic children. Motor sequels were present in 92% of the sample. The static functional activities, as well as dynamic ones, were lower in hypertonic children and higher in hypotonic and normal tone children. Conclusions: Muscle tone exacerbation is more present in hydrocephalus children and motor function is impaired, being the neuropsychomotor development delayed more evident in spastic children group and less pronounced in children with normal muscle tone.